2004
DOI: 10.1080/00268970410001668444
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of the dications HeO2+and He2O2+

Abstract: Employing multireference CI techniques with correlation consistent basis sets, potential energy curves and surfaces for low-lying electronic states of HeO 2þ and He 2 O 2þ are computed. A detailed investigation of the structure and stability properties reveals that both molecular ions are metastable in their respective ground states, namely, 3 AE À for HeO 2þ and 3 AE À g for He 2 O 2þ . Calculating and analysing also potential energy curves of the singly charged diatomic system HeO þ , a picture of He 2 O 2þ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…These are in good agreement with the results obtained by Simpson et al, 9 1.42 mhartree at 4.57 bohr, and by Frenking et al, 13 1.27 mhartree at 4.67 bohr. Hogreve 17 did not report parameters for the 4 ⌺ − state, but found a well depth of 18 mhartree at 2.28 bohr for the 2 ⌸ state, while our calculations gave 17.86 mhartree at 2.253 bohr.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…These are in good agreement with the results obtained by Simpson et al, 9 1.42 mhartree at 4.57 bohr, and by Frenking et al, 13 1.27 mhartree at 4.67 bohr. Hogreve 17 did not report parameters for the 4 ⌺ − state, but found a well depth of 18 mhartree at 2.28 bohr for the 2 ⌸ state, while our calculations gave 17.86 mhartree at 2.253 bohr.…”
Section: Resultsmentioning
confidence: 85%
“…The higher-lying 2 D state yields 2 ⌸, 2 ⌬, and 2 ⌺ − , with the first two having ⍀ =3/2 states that can interact with the 4 ⌺ 3/2 − state. As mentioned previously, Hogreve 17 found that the 2 ⌬ and 2 ⌺ − did not cross the 4 ⌺ − state, that the 2 ⌸ did, but that the crossing was only far up the repulsive wall. ͑The interested reader should consult Fig.…”
Section: Theoretical Detailsmentioning
confidence: 76%
“…As a result, the unique chemistry has largely been unraveled by theoretical means. There have been numerous studies of p-block helide molecular ions, [8][9][10][11] with a recent theoretical interest in helium cluster ions such as He n X 1 (X = Li, Be, Na, Mg, Ca). [12][13][14] In contrast, theoretical investigations of TM-helide molecular ions have been less common.…”
Section: Introductionmentioning
confidence: 99%
“…Helium, for example, can form metastable anions with a FHeX – structure (X = O, S, Se, CC). Additionally, noble gas complexes commonly exhibit fluorine, prompting an ongoing quest for fluorine-free compounds . Investigations into dicationic complexes have largely focused on diatomic , and triatomic molecules ,, with at most two noble gas atoms.…”
mentioning
confidence: 99%